Peran Guru Pendidikan Jasmani Dalam Pembinaan Bakat Olahraga Siswa Melalui Ekstrakurikuler Bola Voli Di Sma Negeri 1 Tenggarong Seberang Tahun Pembelajaran 2025/2026 - Mu'ammar mu'ammar (CENDIKIA, 2026)
This study aimed to determine the role of Physical Education, Sports, and Health (PE) teachers in developing students' sports talents through volleyball extracurricular activities at State Senior High School 1 Tenggarong Seberang in the 2025/2026 academic year. This study employed a descriptive qualitative research method involving the principal, Physical Education, Sports, and Health (PE) teachers, and students participating in the volleyball extracurricular program as the research subjects. Data were collected through interviews, observations, and documentation. The findings revealed that Physical Education, Sports, and Health (PE) teachers played important roles as coaches, mentors, motivators, and evaluators in developing students' sports talents. The teachers designed training programs, provided technical and character guidance, motivated students, and conducted regular evaluations of their progress. Although the program faced several challenges, including limited facilities and infrastructure, weather conditions, and funding, the volleyball extracurricular activities continued to run effectively through the support of the school and collaboration with parents. In conclusion, Physical Education, Sports, and Health (PE) teachers play a vital role in fostering and developing students' sports talents through volleyball extracurricular activities, thereby improving students' skills and sports achievements.